Barnhöft: a hip specific 6-item questionnaire for children - Bengt Herngren; Margaretha Stenmarker; Karin Enskär (SpringerOpen, 2017)
Abstract Background Health-related quality of life instruments, both general and more disease specific, would ideally be included in the evaluation of outcome in paediatric orthopaedics. The aim of this study was to translate and culturally adapt an instrument measuring hip function and pain for Swedish children 8-15 years old with a hip disorder. Methods Translation of an established questionnaire for hip disorder in children, CHOHES, was performed and called Barnhöft. Retrospective and cognitive debriefing interviews were conducted with 15 healthy children to test for the comprehensibility of the instrument. Children with slipped capital femoral epiphysis (n = 25) and healthy children (n = 35) participated in further testing through test-retest and with the comparison of answers given in a general health-related quality of life test, EQ-5D-Y ( www.euroqol.org ). A multi-professional expert committee supervised the process and judged the content validity. Results The test-retest method with a weighted Cohen's kappa showed a good stability of the instrument. The construct validity for the pain domain (1-item) in EQ-5D-Y compared to the pain domain in Barnhöft showed a Spearman's correlation coefficient of 0.73. The degree of hip pain in Barnhöft was also compared with the item "doing usual activities" in EQ-5D-Y with a Spearman's correlation coefficient of 0.67. Conclusion Barnhöft could be used as a simple 6-item questionnaire to identify children with pain and/or functional limitations due to sequelae related to a hip disease in childhood.